2000
DOI: 10.1088/0953-8984/12/8/328
|View full text |Cite
|
Sign up to set email alerts
|

Off-centre dynamic Jahn-Teller effect studied by electron spin relaxation of Cu2+ions in SrF2crystal

Abstract: Temperature cw-EPR and pulsed EPR electron spin echo experiments were performed for a low concentration of Cu2+ ions in cubic SrF2 crystals. The well resolved EPR spectrum at low temperatures (below 30 K) with parameters g = 2.493, g = 2.083, A = 121, A = 8.7, A (19 F) = 135, A (19 F) = 33.0 (A -values in 10-4 cm-1 ) is transformed continuously into a single broad line above 225 K on heating, due to the g -factor shift and EPR line broadening. These data along with the angular variation EPR data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…In fact, for other fluorite-type crystals doped with d 9 ions, the large off-centre shift (≈ 3.10 Å/2−∆Z ≈ 1.35 Å for the studied system) was also found, e.g. Cu 2+ ion SrCl 2 (≈ 1.35 Å) [2], Ni + ion in CaF 2 (≈ 0.99 Å) [6] and SrF 2 (≈ 1.08 Å) [7]. Therefore, the local structure parameter ∆Z of the impurity Cu 2+ center in BaF 2 obtained in this work can be regarded as reasonable.…”
Section: +supporting
confidence: 53%
See 1 more Smart Citation
“…In fact, for other fluorite-type crystals doped with d 9 ions, the large off-centre shift (≈ 3.10 Å/2−∆Z ≈ 1.35 Å for the studied system) was also found, e.g. Cu 2+ ion SrCl 2 (≈ 1.35 Å) [2], Ni + ion in CaF 2 (≈ 0.99 Å) [6] and SrF 2 (≈ 1.08 Å) [7]. Therefore, the local structure parameter ∆Z of the impurity Cu 2+ center in BaF 2 obtained in this work can be regarded as reasonable.…”
Section: +supporting
confidence: 53%
“…Many paramagnetic ions (such as Cu 2+ [1][2][3][4], Ag 2+ [5], Ni + [6,7], Cr 2+ [8], Mn 2+ [9], Fe 3+ [10,11], Ce 3+ [12], Ti 3+ [13]) have been introduced into cubic fluorite-type crystals to study the local structure of the host lattice and the electronic properties of paramagnetic impurities in these crystals by means of electron paramagnetic resonance (EPR) technique, which would be useful to understand the properties (such as optical and luminescent properties) of crystals containing ions. Based on the EPR experiments and theoretical studies, it is found that the local structures around many paramagnetic centers in these crystals are of tetragonal symmetry or orthorhombic symmetry [8].…”
Section: Introductionmentioning
confidence: 99%
“…8). The dephasing of the precessional spin motion due to this mechanism has not been considered theoretically in detail, but it was suggested (48) and observed by us for Cu 2+ ions in different crystals (5,20,39). The possible excitations and relaxation back within the same potential well (Orbach-Aminov-type process) do not operate, since then w should be on the order of the vibrational frequency 10 13 s −1 .…”
Section: Temperature Dependence Of the Dephasing Ratementioning
confidence: 95%
“…However, the difference in ionic radii of host and guest ions and the difference in their electronic structure can produce a local distortion and host lattice relaxation around the impurity ion. Cu 2þ ions in SrF 2 [15,16] and in BaF 2 [8] are off-center shifted due to Jahn-Teller or pseudo-Jahn-Teller effect [17]. Ti 2þ ion ð3d 2 ; S ¼ 1Þ in the cubic environment has orbitally non-degenerate ground state, thus it is not the Jahn-Teller active ion and off-center shift is not expected.…”
Section: Introductionmentioning
confidence: 99%